Interleukin-25 Induces Resistance Against Intestinal Trematodes - Muñoz-Antoli, Carla (Sci Rep, 2016)
Echinostoma caproni is an intestinal trematode that has been extensively used as an experimental model to investigate the factors determining the resistance to intestinal helminths or the development of chronic infections. ICR mice are permissive hosts for E. caproni in which chronic infections are developed, concomitantly with local Th1 responses, elevated levels of local IFN-γ, inflammation and antibody responses. However, mice develop partial resistance to homologous challenge infections after cure of a primary infection, which converts this subject into an adequate model for the study of the mechanisms generating resistance against intestinal helminths. The purpose of the present study was to compare the immune response induced in primary and secondary infections to elucidate the factors determining the different outcome of the infection in each type of infection. The results obtained indicate that susceptibility is determined by the lack of IL-25 expression in response to primary infection. In contrast, infection in an environment with elevated levels of IL-25, as occurs in challenge infection, results in a Th2 phenotype impairing parasite survival. This was confirmed by treatment of naïve mice with exogenous IL-25 and subsequent infection. Changes induced in goblet cell populations and mucin glycosylation could be implicated in resistance to infection.